FGF2 Is Protective Towards Cisplatin-Induced KGN Cell Toxicity by Promoting FTO Expression and Autophagy - Wang, Rongli; Wang, Lijun; Wang, Lihui; Cui, Zhiwei; Cheng, Feiyan; Wang, Wei; Yang, Xinyuan (Frontiers in Endocrinology, 2022)
It’s widely known that chemotherapy-induced apoptosis of granulosa was the main reason for premature ovarian failure (POF). And accumulating evidence has demonstrated that autophagy was involved in it. Studies before have reported that fibroblast growth factor-2 (FGF2) could attenuate cell death via regulating autophagy. And in our previous study, FGF2 could decrease granulosa cell apoptosis in cisplatin-induced POF mice. Furthermore, obesity-associated protein (FTO), which decreased significantly in POF mice, could inhibit cell apoptosis via activating autophagy. And down-regulation of FTO could decrease the expression of paracrine factor FGF2. However, the relationship between FTO and FGF2 in granulosa cell autophagy is still unknown. In the present study, CCK-8 and EdU assays showed that exogenous addition FGF2 could promote cisplatin-induced injured granulosa cell proliferation. Western blotting indicated that FGF2 could inhibit apoptosis of injured granulosa cells via autophagy. Inhibition of autophagy by chemicals suppressed the effect of FGF2 and promoted injured cells apoptosis. In addition, the expression of FTO was decreased in injured cells, and FGF2 addition could reverse it. And overexpression of FTO reduced injured cells apoptosis via activating the autophagy process. Our finds indicated that FGF2 activates autophagy by regulating the expression of FTO, thereby reducing the apoptosis of the injured cells.